(untitled) (The Review of Diabetic Studies, 2025)
Background: The Kingdom of Saudi Arabia (KSA) has prioritized patient safety as a cornerstone of its "Vision 2030" healthcare transformation. Within the military healthcare sector—noted for its high-volume, high-stakes environments—maintaining a robust Patient Safety Culture (PSC) is critical. While many studies focus broadly on physicians and bedside nurses, the specific contributions and perceptions of the multidisciplinary team—including radiology, pharmacy, and emergency medical services—are vital for a holistic understanding of systemic safety. Objective: This systematic review aims to synthesize current evidence regarding the perceptions, barriers, and facilitators of patient safety culture among diverse healthcare professionals (Nursing, Epidemiology, Radiology, Paramedics, Operating Room teams, and Pharmacy Technicians) within Saudi military hospitals. Methods: A systematic search was conducted across major databases (PubMed, CINAHL, Google Scholar, and Saudi Digital Library) for studies published between 2014 and 2024. Inclusion criteria focused on empirical studies utilizing validated tools, such as the Hospital Survey on Patient Safety Culture (HSOPSC), specifically within the Saudi military medical context. Results: Preliminary findings indicate a moderate perception of patient safety culture across the Saudi military sector, characterized by strong teamwork and managerial support but hindered by a persistent "blame culture," staffing shortages leading to burnout, and critical communication gaps during specialty-specific transitions in pharmacy, radiology, and operative care. Conclusion: While Saudi military healthcare facilities demonstrate a strong foundational commitment to safety, improving the non-punitive reporting environment and addressing staffing shortages are essential for moving from "compliance" to a "culture of safety." Future interventions should be tailored to the unique workflows of paramedical and technical staff, rather than relying on nursing-centric models alone.